2014
DOI: 10.1016/j.apcatb.2014.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high surface area TiO2 nanoparticles by mild acid treatment with HCl or HI for photocatalytic propene oxidation

Abstract: Elsevier Ouzzine, M.; Maciá Agulló, JA.; Lillo-Ródenas, MA.; Quijada Tomás, C.; Linares-Solano, A. (2014). Synthesis of high surface area TiO2 nanoparticles by mild acid treatment with HCl or HI for photocatalytic propene oxidation. Applied Catalysis B: Environmental. 154-155:285-293. doi:10.1016/j.apcatb.2014 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…10b) can be used to evaluate the band gaps of the synthetic samples which are indirect semiconductors. As a result, their (Das et al 2010;Ouzzine et al 2014) indicated that higher surface area of TiO 2 improves the absorption of more water molecules on the surface and the higher crystalline but smaller particle size results in an efficient utilization of charge carriers, while the photogenerated carriers diffuse rapidly to the surface and reacts quickly with the adsorbed water molecules. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…10b) can be used to evaluate the band gaps of the synthetic samples which are indirect semiconductors. As a result, their (Das et al 2010;Ouzzine et al 2014) indicated that higher surface area of TiO 2 improves the absorption of more water molecules on the surface and the higher crystalline but smaller particle size results in an efficient utilization of charge carriers, while the photogenerated carriers diffuse rapidly to the surface and reacts quickly with the adsorbed water molecules. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Initially, fluoroplastic (type F-3MV, F-32LN) and silicone varnishes (type KO-85) were investigated as a transparent layer by Bespalova et al [44]. The most promising of them was the 1 -3 mass% solution of F-32LN fluoroplastic varnish.…”
Section: Selective Composite Oxide Coatingsmentioning
confidence: 99%
“…Nanostructured coatings based on titanium oxide were obtained as a result of electrophoretic deposition under the influence of an asymmetrical alternating current [16]. This method also has a number of advantages compared to other widely-used nanocrystal titanium dioxide methods [40][41][42][43][44][45]. It should be noted that the use of an asymmetric alternating current for these purposes allowed suppression of gas bubble formation due to the absence of electrolysis of water on electrodes, and obviated the need for using organic stabilizers in the electrolyte-suspension.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known TiO2 nanoparticles with good physico-chemical properties are mainly dominated by three phasesnamely anatase, rutile and brookite. On a nanometer scale or in a thin layer form,TiO 2 nanoparticles are transparent and have a wide surface area [3]. To improve the performance of thin film TiO 2 for photovoltaics application purpose such as dye sensitized solar cell, TiO 2 layer has been modified by the addingmetal dopant such as Fe [4] and Zn [5].…”
Section: Introductionmentioning
confidence: 99%